A CuMgScO-type hydrotalcite catalyst and its preparation method and application

By preparing CuMgScO hydrotalcite catalyst, the high pressure and high solvent dosage problems of DMCD hydrogenation in the prior art were solved, and the catalyst performance with efficient conversion and long life under low pressure is achieved, which is suitable for the production of high-end polyester materials.

CN116943667BActive Publication Date: 2025-08-19ZHEJIANG HENGYI PETROCHEMICAL RES INST CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310761415.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-26
Publication Date
2025-08-19
Estimated Expiration
2043-06-26

AI Technical Summary

Technical Problem

The existing catalysts for preparing CHDM with DMCD hydrogenation have problems such as high reaction pressure, large solvent usage and cumbersome preparation process, and the catalyst stability and service life are insufficient.

Method used

The CuMgScO hydrotalcite catalyst was prepared by using Sc as a trivalent ion. The layered plate-like structure was formed by calcining treatment, which improved the dispersion and stability of copper, avoided agglomeration, and used for the DMCD hydrogenation reaction, and controlled the reaction conditions to reduce the amount of solvent.

Benefits of technology

It realizes efficient conversion of DMCD to CHDM under low pressure, has high product conversion and selectivity, and has a long catalyst life. It is suitable for the preparation of 1,4-cyclohexanedimethanol by hydrogenation of dimethyl 1,4-cyclohexanedimethanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116943667B_ABST
    Figure CN116943667B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of catalysts and discloses a CuMgScO type hydrotalcite catalyst and its preparation method and application. The catalyst of the present invention has a lamellar hydrotalcite structure and is composed of Cu x Mg y Sc2O z x = 0.8-1.3, y = 2.7-6.8, z = 6-10, the Cu content in the catalyst is ≥ 15.6 wt%, and the ratio of the sum of the mass of Cu and Mg to the mass of Sc is ≤ 2 / 1. This invention, for the first time, uses Sc as a trivalent ion to prepare a hydrotalcite-like precursor and calcines it to produce a CuMgScO hydrotalcite-like catalyst. The preparation method is simple, and the catalyst exhibits a lamellar hydrotalcite-like structure, excellent stability, and a long service life. The catalyst of this invention is used in the hydrogenation of DMCD to CHDM under mild reaction conditions (low reaction pressure), reducing solvent usage while achieving high product conversion and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts, and in particular to a CuMgScO-based hydrotalcite catalyst and a preparation method and application thereof. Background Art

[0002] Plastics are an indispensable part of modern life. Between 1950 and 2015, humans produced more than 8.3 billion tons of polymers, synthetic fibers, and additives, of which approximately 4.6 billion tons have ended up in landfills or been discarded. However, these plastic wastes that enter nature are difficult to degrade and can cause serious pollution. Therefore, the recycling and regeneration of waste plastics is of great significance. Among the many types of plastics, polyethylene terephthalate (PET) has the advantages of being lightweight, durable, and wear-resistant, and has therefore been widely used in industries such as automobiles, textiles, and packaging. However, the widespread use and large-scale consumption of PET materials have placed a serious burden on the environment. A sustainable and economically viable way to alleviate this problem is to recycle and reuse post-consumer PET waste.

[0003] Currently, there are three methods for PET recycling: mechanical recycling, thermal recycling, and chemical recycling. Chemical recycling can extend the lifecycle of monomers, promote energy economy and versatility, and adapt to and meet market demand. At the same time, the raw materials obtained from chemical recycling can reduce the consumption of fossil resources, and therefore have attracted widespread attention from researchers. Chemical recycling methods for PET can be divided into alcoholysis, hydrolysis, and aminolysis. PET can be converted to dimethyl terephthalate (DMT) through methanolysis. This conversion is thorough and has important industrial application value. Furthermore, DMT can be hydrogenated to produce dimethyl 1,4-cyclohexanedicarboxylate (DMCD), and DMCD can be further hydrogenated to produce the higher value-added chemical 1,4-cyclohexanedimethanol (CHDM).

[0004] 1,4-Cyclohexanedimethanol (CHDM) can be used to produce polyester fibers, polyester electrical appliances, unsaturated polyester resins, polyester glazes, polyurethane foams, as well as lubricants and hydraulic fluids. It can also be used to prepare polymers with different melting points by adjusting the ratio of the cis and trans isomers of CHDM. In addition, in the PET production process, partial replacement of ethylene glycol with CHDM can synthesize polyesters with higher glass transition temperatures, increase the transparency, colorability, air tightness, processing properties and low-temperature toughness of polyester materials, and have good application prospects in food packaging, daily chemical products, photochemistry and other fields. my country is a major consumer of polyester, and the domestic consumption of polyester materials has increased year by year, but the development of the polyester raw material industry lags seriously behind the downstream industry; the domestic polyester raw material market is highly dependent on imports. In summary, the development of catalysts and reaction processes for the hydrogenation of DMCD to prepare CHDM is of great significance to the development of the high-end polyester industry.

[0005] In published patents and literature, Eastman Corporation's patents US2901466 and US3334149 used Cu-Cr catalysts to catalyze the hydrogenation of DMCD to produce CHDM. However, the high toxicity of Cr in the catalyst and the harsh conditions used in the patents (20.6-38 MPa) limit the promotion and use of Cu-Cr catalysts and the process.

[0006] Patent publication number CN1398841A discloses a Cu-ZnO-Al2O3 catalyst that achieves a DMCD conversion of 97.2% and a CHDM selectivity of 91.4% under reaction conditions of 6 MPa and 240°C. However, the reaction suffers from drawbacks such as high solvent content (8.8 g DMCD / 100 mL methanol) and low reaction solution processing efficiency (feed rate of 15 mL / h), and the catalyst's service life is not assessed. Patent application publication number CN107188782B discloses a method for preparing a Cu-Zn-Al catalyst by a sedimentation process. This catalyst is used in a two-stage reactor for DMCD hydrogenation. Under reaction conditions of 8.5 MPa and reaction temperatures of 175-180°C and 205-210°C for the first and second stages, respectively, a DMCD conversion of 99.9% and a CHDM selectivity of 98.4% were achieved. However, the reaction suffers from drawbacks such as high hydrogen pressure and a complex reaction process, which increase production costs. Furthermore, the application does not mention the catalyst's service life.

[0007] Yuan Youzhu et al. (Chemical Communiactions, 2017, 53, 6933-6936) synthesized copper phyllosilicate by a hydrothermal method and used it as a precursor to prepare a Cu-SiO2 catalyst. Under reaction conditions such as 220°C and a hydrogen pressure of 5 MPa, the catalyst was able to maintain a CHDM yield of more than 95% for 1000 hours of continuous operation. However, the catalyst preparation process was relatively complicated and tedious, and a large amount of solvent (5% DMCD methanol solution) was used in the reaction. Li Feng et al. (Catalysis Communications, 39 (2013) 96-101) used the nucleation crystallization isolation method to prepare a composite metal oxide and then reduced it to obtain a Cu / ZnO / ZrO2 catalyst with high dispersion properties. The catalyst can obtain a DMCD conversion rate of 99.4% and a CHDM selectivity of 97.4% under reaction conditions such as 220°C and a hydrogen pressure of 8 MPa. However, the catalyst also has the disadvantages of large solvent consumption (10% DMCD methanol solution) and high reaction hydrogen pressure during use. In addition, the paper only provides activity data for the catalyst's stability for 24 hours.

[0008] In summary, the catalysts currently reported in literature and patents for the hydrogenation of DMCD to CHDM suffer from high reaction pressures, large solvent requirements, and complex catalyst preparation processes. Therefore, there is an urgent need to develop a catalyst that is simple to prepare, requires minimal solvent, has low reaction pressures, and exhibits high activity and stability. Summary of the Invention

[0009] In order to solve the above technical problems, the present invention provides a CuMgScO type hydrotalcite catalyst and its preparation method and application. The present invention is the first to use Sc as a trivalent ion to prepare a hydrotalcite precursor and then calcine to obtain a CuMgScO type hydrotalcite catalyst. The preparation method is simple, and the obtained catalyst has a lamellar hydrotalcite structure, in which the active metal copper is highly dispersed and supported by the Mg-Sc-O x The mixed oxides are effectively isolated, resulting in excellent stability, resistance to agglomeration, and a long service life. The catalyst of the present invention is used in the hydrogenation of DMCD to CHDM under mild reaction conditions (low reaction pressure), which can reduce solvent usage. It also prevents dehydration, hydrogenation, and alkylation of the target product, CHDM, resulting in high product conversion and selectivity.

[0010] The specific technical solutions of the present invention are:

[0011] In the first aspect, the present invention provides a CuMgScO-type hydrotalcite catalyst having a lamellar hydrotalcite-like structure, composed of Cu x Mg y Sc2O z ; wherein x = 0.8 ~ 1.3, y = 2.7 ~ 6.8, z = 6 ~ 10, and the Cu content in the catalyst is ≥ 15.6wt%, and the ratio of the sum of the mass of Cu and Mg to the mass of Sc is ≤ 2 / 1.

[0012] The present invention is the first to use the IIIB group element Sc as a trivalent ion (replacing the traditional Al 3+ Cr 3+ 、Fe 3+ 、Mn 3+ 、Co 3+ ) to prepare hydrotalcite-like catalysts, which can effectively overcome the acidity brought by traditional trivalent metals and increase the interaction between copper and the carrier; therefore, the active metal copper in the catalyst has a high dispersion and can be supported by the carrier Mg-Sc-O x The mixed oxides are effectively isolated, highly stable, and not easily agglomerated, exhibiting a long service life. The catalyst of the present invention is used in the hydrogenation of DMCD to CHDM under mild reaction conditions (low reaction pressure), which can reduce solvent usage. It also prevents dehydration, hydrogenation, and alkylation of the target product, CHDM, resulting in high product conversion and selectivity.

[0013] Furthermore, the present invention has found that the following factors can significantly affect the performance of the catalyst:

[0014] (1) (Cu+Mg) / Sc ratio: The present invention has found that as the (Cu+Mg) / Sc ratio in the catalyst increases, the catalyst hydrogenation activity decreases accordingly. When (Cu+Mg) / Sc≤2 / 1, the DMCD hydrogenation activity is better, and a higher DMCD conversion rate and CHDM selectivity can be obtained. This is because when (Cu+Mg) / Sc≤2 / 1, the hydrotalcite formed in the catalyst precursor has a clear structure, and copper, magnesium, Sc, etc. are evenly dispersed. In addition, the basicity of the catalyst is stronger at this ratio.

[0015] (2) Cu content: The present invention has found that the conversion of DMCD increases with increasing copper content. When the copper content is ≥15.6 wt%, the catalyst has good hydrogenation activity, and a high DMCD conversion rate and CHDM selectivity can be obtained. This is because Cu is the main hydrogenation active center in the catalyst. Increasing the copper content can promote hydrogen activation and accelerate the conversion of reactants.

[0016] Preferably, the contents of Cu, Mg and Sc in the catalyst are 15.6-25.1 wt%, 19.9-33.9 wt% and 18.4-28.3 wt% respectively, and the ratio of the sum of the mass of Cu and Mg to the mass of Sc is ≤2 / 1.

[0017] In a second aspect, the present invention provides a method for preparing a CuMgScO-type hydrotalcite catalyst, comprising the following steps: 1) dissolving a copper salt, a magnesium salt, and a scandium salt in water to obtain a solution A.

[0018] 2) Sodium hydroxide and sodium carbonate are dissolved in water to obtain solution B.

[0019] 3) Solution A and solution B are simultaneously added dropwise to the reactor under stirring, and the pH value of the reaction solution is controlled to be 8.0-10.5. After the reaction, a suspension is obtained.

[0020] 4) The suspension is subjected to hydrothermal crystallization; the crystallization temperature is 80-120° C., and the crystallization time is 8-24 h.

[0021] 5) The solid obtained in step 4) is filtered, washed until the filtrate is neutral, and then dried.

[0022] 6) calcining the solid obtained in step 5) in an air atmosphere at a temperature of 300-500° C. for 2-4 h at a heating rate of 1-10° C. / min to obtain a CuMgScO-type hydrotalcite catalyst.

[0023] The present invention is the first to use Sc as a trivalent ion (replacing the traditional Al 3+ Cr3+ 、Fe 3+ 、Mn3 + 、Co 3+ ) Preparation of hydrotalcite-like precursor (Cu x Mg y Sc2(OH) z The catalyst obtained by calcining the catalyst is simple to prepare, can remove the acidity of traditional hydrotalcite-derived catalysts, prevent the dehydration, hydrogenation, alkylation, etc. of the target product CHDM, and can effectively improve the life of the catalyst.

[0024] Preferably, in step 1), the copper salt is copper nitrate, the magnesium salt is magnesium nitrate, and the scandium salt is scandium chloride.

[0025] Preferably, in step 1), the copper ion concentration in the solution A is 0.02-0.12 mol / L, the magnesium ion concentration is 0.17-0.70 mol / L, and the scandium ion concentration is 0.03-0.30 mol / L.

[0026] Preferably, in step 2), the concentration of sodium hydroxide in the solution B is 0.5-1.0 mol / L, and the concentration of sodium carbonate is 0.1-0.5 mol / L.

[0027] Preferably, in step 3), the volume ratio of solution A to solution B is 1:(0.8-1.2).

[0028] Preferably, in step 3), the stirring condition is stirring at room temperature for 1 to 2 hours.

[0029] Preferably, in step 5), the drying temperature is 50-100° C. and the drying time is 12-24 hours.

[0030] In a third aspect, the present invention provides the use of a CuMgScO-type hydrotalcite catalyst in the hydrogenation of dimethyl 1,4-cyclohexanedicarboxylate to produce 1,4-cyclohexanedimethanol.

[0031] In a fourth aspect, the present invention provides a method for preparing 1,4-cyclohexanedimethanol by hydrogenating dimethyl 1,4-cyclohexanedicarboxylate, comprising the following steps: loading a CuMgScO-type hydrotalcite catalyst into a fixed-bed reactor and introducing a hydrogen flow for reduction treatment; then conducting a hydrogenation reaction under the conditions of introducing hydrogen, dimethyl 1,4-cyclohexanedicarboxylate, and a solvent to produce 1,4-cyclohexanedimethanol.

[0032] Preferably, the reduction treatment is performed at a temperature of 200 to 400° C. and for a time of 1 to 3 hours.

[0033] Preferably, the feed concentration of dimethyl 1,4-cyclohexanedicarboxylate is 5-20 wt %. The temperature of the hydrogenation reaction is 230-250° C., the hydrogen pressure is 2.5-8.0 MPa, and the weight hourly space velocity of dimethyl 1,4-cyclohexanedicarboxylate is 0.08-1.68 h -1 .

[0034] The present invention found that in order to further improve the conversion rate and selectivity of the product, it is necessary to optimize the following process parameters:

[0035] (1) Reaction temperature: The catalyst of the present invention has good activity for the DMCD hydrogenation reaction at different temperatures, and appropriately increasing the reaction temperature can significantly increase the conversion rate of DMCD. However, the selectivity of the target product reaches the highest at 230-250°C.

[0036] (2) The catalyst of the present invention has good DMCD hydrogenation reaction activity at a relatively low hydrogen pressure (2.5-8.0 MPa), and increasing the hydrogen pressure can further increase the activity; when the hydrogen pressure is 2.5 MPa, DMCD can be basically completely converted into CHDM.

[0037] (3) The catalyst of the present invention is heated at different space velocities (0.08-1.68 h -1 ) has good activity and CHDM selectivity for DMCD hydrogenation reaction.

[0038] (4) It shows that the catalyst of the present invention has good DMCD hydrogenation activity when the feed concentration of dimethyl 1,4-cyclohexanedicarboxylate is 5 to 20 wt%, and can obtain a higher DMCD conversion rate and CHDM selectivity.

[0039] Preferably, the solvent is dioxane, cyclohexane, methanol or isopropanol.

[0040] This indicates that the catalyst of the present invention has better DMCD hydrogenation activity when the solvent is dioxane, cyclohexane, methanol or isopropanol.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] (1) The present invention is the first to use Sc as a trivalent ion to prepare a hydrotalcite-like precursor and to obtain a CuMgScO hydrotalcite-like catalyst by calcination. The preparation method is simple, and the obtained catalyst has a lamellar hydrotalcite-like structure, in which the active metal copper is highly dispersed and supported by the Mg-Sc-O x The mixed oxides are effectively isolated, thus having excellent stability, not easy to agglomerate, and having an excellent service life (maintaining more than 1000 hours).

[0043] (2) The catalyst of the present invention is used for hydrogenation of DMCD to CHDM. The reaction conditions are mild (reaction pressure is low), which can reduce the amount of solvent used. At the same time, it can also prevent the dehydration, hydrogenation, alkylation, etc. of the target product CHDM, and the product conversion rate and selectivity are high. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 Scanning electron microscope (SEM) photograph of the catalyst precursor prepared in Example 1.

[0045] Figure 2 XRD pattern of the catalyst precursor prepared in Example 1.

[0046] Figure 3 Schematic diagram of the structure of the catalyst prepared in Example 1. DETAILED DESCRIPTION

[0047] The present invention will be further described below with reference to the embodiments.

[0048] Overall embodiment

[0049] A CuMgScO-type hydrotalcite catalyst having a lamellar hydrotalcite-like structure, composed of Cu x Mg y Sc2O z wherein x=0.8-1.3, y=2.7-6.8, z=6-10, and the content of Cu in the catalyst is ≥15.6wt%, and the ratio of the sum of the mass of Cu and Mg to the mass of Sc is ≤2 / 1. Preferably, the contents of Cu, Mg, and Sc in the catalyst are 15.6-25.1wt%, 19.9-33.9wt%, and 18.4-28.3wt%, respectively, and the ratio of the sum of the mass of Cu and Mg to the mass of Sc is ≤2 / 1.

[0050] A method for preparing a CuMgScO-type hydrotalcite catalyst comprises the following steps:

[0051] 1) Dissolve a copper salt, a magnesium salt, and a scandium salt in water to obtain a solution A. Preferably, the copper salt is copper nitrate, the magnesium salt is magnesium nitrate, and the scandium salt is scandium chloride; the copper ion concentration is 0.02-0.12 mol / L, the magnesium ion concentration is 0.17-0.70 mol / L, and the scandium ion concentration is 0.03-0.30 mol / L.

[0052] 2) Sodium hydroxide and sodium carbonate are dissolved in water to obtain solution B. The concentration of sodium hydroxide is 0.5-1.0 mol / L, and the concentration of sodium carbonate is 0.1-0.5 mol / L.

[0053] 3) Solution A and solution B are simultaneously added dropwise to the reactor at a volume ratio of 1:(0.8-1.2) under stirring at room temperature for 1-2 hours, and the pH value of the reaction solution is controlled at 8.0-10.5 to obtain a suspension after the reaction.

[0054] 4) The suspension is subjected to hydrothermal crystallization (80-120° C., 8-24 h).

[0055] 5) The solid obtained in step 4) is filtered, washed until the filtrate is neutral, and then dried (50-100° C., 12-24 h).

[0056] 6) calcining the solid obtained in step 5) in an air atmosphere (300-500° C., 2-4 h, heating rate of 1-10° C. / min) to obtain a CuMgScO-type hydrotalcite catalyst.

[0057] A method for preparing 1,4-cyclohexanedimethanol by hydrogenating dimethyl 1,4-cyclohexanedicarboxylate comprises the following steps: loading a CuMgScO-type hydrotalcite catalyst into a fixed bed reactor, introducing a hydrogen flow and performing a reduction treatment at 200-400° C. for 1-3 hours; then introducing hydrogen (2.5-8.0 MPa) and dimethyl 1,4-cyclohexanedicarboxylate (feed concentration 5-20 wt%, 0.08-1.68 h) into the reactor, and performing a reduction treatment at 200-400° C. for 1-3 hours; -1 ) and a solvent (preferably dioxane, cyclohexane, methanol or isopropanol) are subjected to hydrogenation reaction at 230-250° C. to obtain 1,4-cyclohexanedimethanol.

[0058] Example 1

[0059] Dissolve 12.97 g of ScCl3·6H2O, 5.08 g of Cu(NO3)2·3H2O, and 20.51 g of Mg(NO3)2·6H2O in 400 mL of deionized water, and stir to dissolve evenly to obtain solution A; dissolve 12.80 g of NaOH and 10.60 g of Na2CO3 in 400 mL of deionized water, and stir to dissolve evenly to obtain solution B.

[0060] At room temperature and under continuous stirring, solution A and solution B were titrated into a beaker simultaneously. The pH of the mixed solution was controlled at about 9.5 during the titration process. After the titration was completed, the resulting suspension was transferred to a 1000 mL hydrothermal kettle and hydrothermally crystallized at 100°C for 14 hours. The resulting solid was then filtered and washed with deionized water until the filtrate was neutral. The solid was then placed in an oven at 80°C and dried for 12 hours. The solid was placed in a crucible. The morphology of the catalyst precursor obtained at this time was as shown below. Figure 1 The crystal structure is shown in Figure 2The sample was calcined at 400°C for 4 hours in a static air atmosphere at a heating rate of 5°C / min. After the temperature dropped to room temperature, the sample was taken out and represented by catalyst A (the schematic diagram of the catalyst structure is shown in FIG. Figure 3 Catalyst A was pressed into tablets and solid particles of 40-60 mesh size were screened out for use in activity testing.

[0061] 1.0 g of the pelletized catalyst A was weighed and reacted continuously in a stainless steel vertical reaction tube with an inner diameter of 12 mm and a length of 550 mm. The ends of the tube were sealed with quartz wool and quartz sand. The catalyst was activated in situ in a hydrogen flow (80 mL / min) at 300°C at normal pressure for 1 h. The temperature was then lowered to the reaction temperature of 250°C and the hydrogen pressure was adjusted to 2 MPa. A 20 wt% DMCD dioxane solution was added to the reaction tube at a WHSV flow rate. DMCD =1.2h -1 The reaction mixture was injected into the reaction tube at a space velocity of 1.5 s. After the reaction temperature reached 100 °C, the reaction solution was collected and further analyzed by capillary gas chromatography. The reaction results are shown in Table 1.

[0062] Example 2

[0063] Similar catalyst preparation steps and the same reaction steps and reaction conditions as in Example 1 were used, except that during the catalyst preparation process, the mass of Cu(NO3)2·3H2O was 6.03 and 7.23 g, and the mass of Mg(NO3)2·6H2O was 32.05 and 43.59 g, respectively. That is, the copper content in the catalyst was maintained at approximately 15%, and the (Cu+Mg) / Sc ratio was changed to 3 / 1 and 4 / 1, respectively. These two catalysts are designated as Catalysts B and C, respectively. Using the same catalyst activity evaluation apparatus and process conditions as in Example 1, the activities of catalysts with different (Cu+Mg) / Sc ratios in DMCD hydrogenation were obtained, as shown in Table 1.

[0064] Table 1 Activity of different (Cu+Mg) / Sc catalysts in DMCD hydrogenation reaction

[0065] Catalyst No. A B C (Cu+Mg) / Sc (molar ratio) 2 / 1 3 / 1 4 / 1 DMCD conversion rate (%) 82.2 51.0 63.5 CHDM selectivity (%) 90.0 73.9 78.3

[0066] Conclusion: The results in Table 1 show that as Cu x Mg y Sc2O z As the (Cu+Mg) / Sc ratio of the catalyst increases, the catalyst hydrogenation activity decreases. When the (Cu+Mg) / Sc ratio is 2 / 1, the DMCD hydrogenation activity is the best, achieving a DMCD conversion rate of 88.2% and a CHDM selectivity of 90.0%.

[0067] Example 3

[0068] Similar catalyst preparation steps and reaction steps and conditions were used as in Example 1, except that during the catalyst preparation, the masses of Cu(NO₃)₂·3H₂O were 3.01, 6.02, and 7.83 g, and the masses of Mg(NO₃)₂·6H₂O were 22.44, 19.23, and 17.31 g, respectively. Thus, the (Cu+Mg) / Sc ratio in the fixed catalysts was 2 / 1. The copper content in the catalysts was varied, and the three catalysts are designated as Catalysts D, E, and F, respectively. The activities of the catalysts with different copper contents in the DMCD hydrogenation are shown in Table 2.

[0069] Table 2 Activity of catalysts with different copper contents in DMCD hydrogenation reaction

[0070] Catalyst No. D A E F Catalyst copper content (wt%) 10.2 16.0 19.7 25.1 DMCD conversion rate (%) 47.5 82.2 95.3 94.9 CHDM selectivity (%) 70.5 90.0 90.0 88.6

[0071] Conclusion: The results in Table 2 show that the use of Cu x Mg y Sc2O z The catalyst was used in the hydrogenation of DMCD to produce CHDM. DMCD conversion increased with increasing copper content. When the copper content was 19.7%, the catalyst exhibited the best hydrogenation activity, achieving a DMCD conversion of 95.3% and a CHDM selectivity of 90.0%.

[0072] Example 4

[0073] The same catalyst preparation steps, reaction steps, and similar reaction conditions as in Example 1 were used, except that the reaction temperature was changed to 210-290° C. The DMCD hydrogenation activities at different temperatures are shown in Table 3.

[0074] Table 3 DMCD hydrogenation activity at different temperatures

[0075] Reaction temperature / ℃ 210 230 250 270 290 DMCD conversion rate (%) 74.3 99.6 99.7 99.9 99.9 CHDM selectivity (%) 85.8 96.9 96.2 92.3 86.2

[0076] Conclusion: The results in Table 3 show that the Cu x Mg y Sc2O z The catalyst has good activity for DMCD hydrogenation reaction at different temperatures, and appropriately increasing the reaction temperature can significantly increase the conversion rate of DMCD. However, the selectivity of the target product reaches the highest at 230-250℃.

[0077] Example 5

[0078] The same catalyst preparation steps, reaction steps, and similar reaction conditions as in Example 1 were used, except that the hydrogen pressure was varied from 1.0 to 8.0 MPa. The hydrogenation activities of DMCD at different hydrogen pressures are shown in Table 4.

[0079] Table 4 Activity of DMCD hydrogenation at different hydrogen pressures

[0080] Hydrogen pressure / MPa 1.0 2.5 4.0 6.0 8.0 DMCD conversion rate (%) 75.5 97.5 99.7 99.8 99.7 CHDM selectivity (%) 92.0 96.6 96.2 96.2 95.1

[0081] Conclusion: The results in Table 4 show that the Cu x Mg y Sc2O z The catalyst already has good DMCD hydrogenation reaction activity at a relatively low hydrogen pressure, and increasing the hydrogen pressure can further increase the activity; when the hydrogen pressure is 2.5MPa, DMCD can be basically completely converted into CHDM.

[0082] Example 6

[0083] The same preparation steps, reaction steps and similar reaction conditions as those of Catalyst E in Example 3 were used, except that the weight hourly space velocity of DMCD (WHSVDMCD) was changed to 0.08-1.68h -1 The activity of DMCD hydrogenation under different WHSVDMCD is shown in Table 5.

[0084] Table 5 Different WHSV DMCD Activity of DMCD hydrogenation under

[0085] <![CDATA[WHSV DMCD (h -1 )]]> 0.08 0.40 0.80 1.20 1.68 DMCD conversion rate (%) 99.8 100.0 99.9 99.2 97.3 CHDM selectivity (%) 94.1 96.3 97.0 96.5 95.8

[0086] Conclusion: The results in Table 5 show that the Cu x Mg y Sc2O z The catalyst has good activity and CHDM selectivity for DMCD hydrogenation reaction at different space velocities.

[0087] Example 7

[0088] The same preparation steps, reaction steps, and reaction conditions as those for Catalyst E in Example 3 were used, except that the solvent used in the reaction solution was changed to methanol, isopropanol, and cyclohexane, respectively. The DMCD hydrogenation activities in different solvents are shown in Table 6.

[0089] Table 6 Activity of DMCD hydrogenation in different solvents

[0090] solvent Dioxane Methanol Isopropyl alcohol Cyclohexane DMCD conversion rate (%) 99.9 98.9 98.9 99.0 CHDM selectivity (%) 96.8 83.2 94.8 94.8

[0091] Conclusion: The results in Table 6 show that the Cu x Mg y Sc2O z The catalyst has good DMCD hydrogenation activity in various other solvents. In actual production, choosing the right solvent can reduce production costs.

[0092] Example 8

[0093] The same preparation steps, reaction steps and similar reaction conditions as those of Catalyst E in Example 3 were used, except that the concentration of the reaction solution was changed to 5%, 15%, 30% and 40%. The activities are shown in Table 7.

[0094] Table 7 DMCD hydrogenation activity at different feed concentrations

[0095] Feed concentration (wt%) 5 15 20 30 40 DMCD conversion rate (%) 97.8 99.9 99.1 90.2 87.5 CHDM selectivity (%) 97.0 96.8 94.4 92.3 89.9

[0096] Conclusion: The results in Table 7 show that the Cu x Mg y Sc2O z The catalyst still has good DMCD hydrogenation activity when the reaction solution concentration is increased, and the highest DMCD conversion rate and CHDM selectivity can be obtained by selecting an appropriate concentration (5-15%).

[0097] Example 9

[0098] The same preparation steps, reaction steps and reaction conditions as those of Catalyst E in Example 3 were used to investigate the stability of the catalyst under continuous reaction for 1000 h. The DMCD hydrogenation activity obtained is shown in Table 8.

[0099] Table 8 DMCD hydrogenation activity at different reaction times

[0100] Reaction time / h DMCD conversion rate (%) CHDM selectivity (%) 2 99.3 94.8 50 99.7 96.2 200 99.3 95.6 400 99.2 95.9 600 99.6 94.8 800 99.9 96.3 1000 99.8 96.1

[0101] Conclusion: The results in Table 8 show that the Cu x Mg y Sc2O z The catalyst has excellent reaction activity and stability in the DMCD hydrogenation reaction, and no significant decrease in activity was observed after continuous operation for 1000 hours.

[0102] Comparative Example 1

[0103] Dissolve 18.76 g of Al(NO3)3·9H2O, 5.08 g of Cu(NO3)2·3H2O, and 20.51 g of Mg(NO3)2·6H2O in 400 mL of deionized water, and stir to dissolve evenly to obtain solution A; dissolve 12.80 g of NaOH and 10.60 g of Na2CO3 in 400 mL of deionized water, and stir to dissolve evenly to obtain solution B.

[0104] At room temperature and with continuous stirring, solution A and solution B were titrated simultaneously into a beaker, maintaining the pH of the mixture at approximately 9.5. After titration, the resulting suspension was transferred to a 1000mL hydrothermal reactor and hydrothermally crystallized at 100°C for 14 hours. The resulting solid was then filtered and washed with deionized water until the filtrate was neutral. The solid was then dried in an 80°C oven for 12 hours. The solid was placed in a crucible and calcined in a static air atmosphere at 400°C for 4 hours at a heating rate of 5°C / min. After the temperature cooled to room temperature, a sample was removed and designated as catalyst CuMgAlO. The catalyst CuMgAlO was pelletized, and solid particles of 40-60 mesh were screened for activity testing.

[0105] 1.0 g of the pelletized catalyst CuMgAlO was weighed and reacted continuously in a stainless steel vertical reaction tube with an inner diameter of 12 mm and a length of 550 mm. The ends of the tube were sealed with quartz wool and quartz sand. The reaction was carried out in situ reduction activation for 1 h in a hydrogen flow (80 mL / min) at 300°C under normal pressure. The temperature was then lowered to the reaction temperature of 250°C and the hydrogen pressure was adjusted to 2 MPa. A 20 wt% DMCD dioxane solution was added to the reaction tube at a WHSV flow rate. DMCD =1.2h -1 The reaction mixture was injected into the reaction tube at a space velocity of 1.5 s. After the reaction temperature reached 100 °C, the reaction solution was collected and further analyzed by capillary gas chromatography. The reaction results are shown in Table 9.

[0106] Comparative Example 2

[0107] Dissolve 20.01 g of Cr(NO3)3·9H2O, 5.08 g of Cu(NO3)2·3H2O, and 20.51 g of Mg(NO3)2·6H2O in 400 mL of deionized water, and stir to dissolve evenly to obtain solution A; dissolve 12.80 g of NaOH and 10.60 g of Na2CO3 in 400 mL of deionized water, and stir to dissolve evenly to obtain solution B.

[0108] At room temperature and with continuous stirring, solution A and solution B were titrated simultaneously into a beaker, maintaining the pH of the mixture at approximately 9.5. After titration, the resulting suspension was transferred to a 1000mL hydrothermal reactor and hydrothermally crystallized at 100°C for 14 hours. The resulting solid was then filtered and washed with deionized water until the filtrate was neutral. The solid was then dried in an 80°C oven for 12 hours. The solid was placed in a crucible and calcined in a static air atmosphere at 400°C for 4 hours at a heating rate of 5°C / min. After the temperature cooled to room temperature, a sample was removed and designated as catalyst CuMgCrO. The catalyst CuMgCrO was pelletized, and solid particles of 40-60 mesh were screened for activity testing.

[0109] The same activity test method as in Comparative Example 1 was used, and the activity of the catalyst CuMgCrO was shown in Table 9.

[0110] Table 9 Activity of different trivalent metal catalysts in DMCD hydrogenation reaction

[0111] catalyst DMCD conversion rate (%) CHDM selectivity (%) Catalyst A (CuMgScO) 82.2 90.0 Catalyst CuMgAlO 79.6 80.3 Catalyst CuMgCrO 76.2 82.6

[0112] The results in Table 9 show that the use of trivalent metal Sc with strong alkalinity to replace the traditional trivalent metal ion Al 3+ and Cr 3+ The catalyst prepared from the hydrotalcite precursor has higher DMCD conversion rate and selectivity for the target product CHDM.

[0113] Unless otherwise specified, the raw materials and equipment used in the present invention are commonly used in the art; the methods used in the present invention are conventional methods in the art unless otherwise specified.

[0114] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A CuMgScO-type hydrotalcite catalyst, characterized in that: It has a lamellar hydrotalcite-like structure and is composed of Cu x Mg y Sc2O z ; wherein x=0.8~1.3, y=2.7~6.8, z=6~10, and the Cu content in the catalyst is 15.6~25.1wt%, and the ratio of the sum of the mass of Cu and Mg to the mass of Sc is ≤2 / 1.

2. The CuMgScO-type hydrotalcite catalyst according to claim 1, characterized in that: The contents of Cu, Mg and Sc in the catalyst are 15.6-25.1wt%, 19.9-33.9wt% and 18.4-28.3wt% respectively, and the ratio of the sum of the weights of Cu and Mg to the weight of Sc is ≤2 / 1.

3. A method for preparing the CuMgScO-type hydrotalcite catalyst according to claim 1 or 2, characterized in that The following steps are involved: 1) Dissolve copper salt, magnesium salt and scandium salt in water to obtain solution A; 2) Dissolve sodium hydroxide and sodium carbonate in water to obtain solution B; 3) Solution A and Solution B are added dropwise to the reactor simultaneously under stirring, and the pH value of the reaction solution is controlled between 8.0 and 10.5 to obtain a suspension after the reaction; 4) Performing hydrothermal crystallization on the suspension; the crystallization temperature is 80-120°C and the crystallization time is 8-24 hours; 5) filtering the solid obtained in step 4), washing until the filtrate is neutral, and then drying; 6) calcining the solid obtained in step 5) in an air atmosphere at a temperature of 300-500° C. for 2-4 hours at a heating rate of 1-10° C. / min to obtain a CuMgScO-type hydrotalcite catalyst.

4. The preparation method according to claim 3, wherein: In step 1), the copper salt is copper nitrate, the magnesium salt is magnesium nitrate, and the scandium salt is scandium chloride.

5. The preparation method according to claim 3, wherein: In step 1), the copper ion concentration in the solution A is 0.02-0.12 mol / L, the magnesium ion concentration is 0.17-0.70 mol / L, and the scandium ion concentration is 0.03-0.30 mol / L; In step 2), the concentration of sodium hydroxide in the solution B is 0.5-1.0 mol / L, and the concentration of sodium carbonate is 0.1-0.5 mol / L.

6. The preparation method according to claim 5, wherein: In step 3), the volume ratio of solution A to solution B is 1:(0.8~1.2).

7. Use of the CuMgScO-based hydrotalcite catalyst according to claim 1 or 2 or the CuMgScO-based hydrotalcite catalyst obtained by the preparation method according to any one of claims 3 to 6 in the hydrogenation of dimethyl 1,4-cyclohexanedicarboxylate to produce 1,4-cyclohexanedimethanol.

8. A method for preparing 1,4-cyclohexanedimethanol by hydrogenating dimethyl 1,4-cyclohexanedicarboxylate, characterized in that The following steps are involved: A fixed bed reactor is loaded with the CuMgScO-type hydrotalcite catalyst according to claim 1 or 2 or the CuMgScO-type hydrotalcite catalyst obtained by the preparation method according to any one of claims 3 to 6, and a hydrogen flow is introduced for reduction treatment; then, a hydrogenation reaction is carried out under the conditions of hydrogen, dimethyl 1,4-cyclohexanedicarboxylate and a solvent to produce 1,4-cyclohexanedimethanol.

9. The method according to claim 8, wherein: The reduction treatment is performed at a temperature of 200-400° C. and for a time of 1-3 hours.

10. The method according to claim 8, wherein: The feed concentration of dimethyl 1,4-cyclohexanedicarboxylate is 5-20wt%; The hydrogenation reaction temperature is 230-250° C., the hydrogen pressure is 2.5-8.0 MPa, and the weight hourly space velocity of dimethyl 1,4-cyclohexanedicarboxylate is 0.08-1.68 h -1 ; The solvent is dioxane, cyclohexane, methanol or isopropanol.

Citation Information

Patent Citations

  • Method for preparing 1,4-cyclohexanediethanol by hydrogenation of dimethyl 1,4-cyclohexanedicarboxylate

    CN107188782B

  • Catalyst for hydrogenating 1,4-dimethyl hexahydroterephthalate to produce 1,4-dimethyl cyclohexanol and its prepn process

    CN1398841A

  • Linear polyesters and polyester-amides from 1,4-cyclohexanedimethanol

    US2901466A

  • Plural stage hydrogenation of dialkyl terephthalate using palladium and then copper chromite

    US3334149A